2021
DOI: 10.1101/2021.06.14.21258894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread Contamination of SARS-CoV-2 on Highly Touched Surfaces in Brazil During the Second Wave of the COVID-19 Pandemic

Abstract: Although SARS-CoV-2 surface contamination has been investigated in temperate climates, few studies have been conducted in the tropics. Here, we investigated the presence of SARS-CoV-2 on high-touch surfaces in a large city in Brazil. A total of 400 surface samples were collected in February 2021 in the City of Recife, Northeastern Brazil. A total of 97 samples (24.2%) tested positive for SARS-CoV-2 by RT-qPCR using the CDC-USA protocol. All the collection sites, except one (18/19, 94.7%) had at least one envir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…12,127,128 Previous studies conducted under laboratory conditions have shown the ability of SARS-CoV-2 to remain infectious on various surfaces (e.g., paper, glass, and stainless steel) for up to 28 days at 20°C depending on the type of material 129 and in aerosols for up to 3 h. 128 To address this question in real-life settings, many recent studies have investigated the presence of SARS-CoV-2 contamination in the air and on environmental surfaces, including health care units 123,124,130−132 and urban settings. 126,133−135 The results demonstrate different levels of viral contamination varying from high 130,136 to low 132 or even no contamination by SARS-CoV-2 RNA. 134 Additionally, most of the reported positive environmental samples were found to have high reverse transcription quantitative polymerase chain reaction (RT-qPCR) cycle threshold (Ct) values (>30) for most of the positive samples, 130,136 indicating low viral load and the labile nature of SARS-CoV-2 in the environment.…”
Section: ■ Modes Of Transmissionmentioning
confidence: 98%
See 1 more Smart Citation
“…12,127,128 Previous studies conducted under laboratory conditions have shown the ability of SARS-CoV-2 to remain infectious on various surfaces (e.g., paper, glass, and stainless steel) for up to 28 days at 20°C depending on the type of material 129 and in aerosols for up to 3 h. 128 To address this question in real-life settings, many recent studies have investigated the presence of SARS-CoV-2 contamination in the air and on environmental surfaces, including health care units 123,124,130−132 and urban settings. 126,133−135 The results demonstrate different levels of viral contamination varying from high 130,136 to low 132 or even no contamination by SARS-CoV-2 RNA. 134 Additionally, most of the reported positive environmental samples were found to have high reverse transcription quantitative polymerase chain reaction (RT-qPCR) cycle threshold (Ct) values (>30) for most of the positive samples, 130,136 indicating low viral load and the labile nature of SARS-CoV-2 in the environment.…”
Section: ■ Modes Of Transmissionmentioning
confidence: 98%
“…126,133−135 The results demonstrate different levels of viral contamination varying from high 130,136 to low 132 or even no contamination by SARS-CoV-2 RNA. 134 Additionally, most of the reported positive environmental samples were found to have high reverse transcription quantitative polymerase chain reaction (RT-qPCR) cycle threshold (Ct) values (>30) for most of the positive samples, 130,136 indicating low viral load and the labile nature of SARS-CoV-2 in the environment. Importantly, the majority of these studies did not investigate the capacity of SARS-CoV-2 to be cultured from an environmental surface sample, which is crucial for understanding the role of SARS-CoV-2 RNA-positive samples in terms of infectious potential toward the human population.…”
Section: ■ Modes Of Transmissionmentioning
confidence: 98%
“…48 Indoor aerosols can negatively affect human health and have attracted growing public attention as people have spent more time indoors during the pandemic of COVID-19. 49,50 Although appropriate filters can remove most of the largesized aerosols, fine and ultrafine aerosol particles of diameters less than 2.5 mm and 0.1 mm respectively still post challenges to human health due to their long diffusing time, high airborne mobility, and large penetration depth in respiratory systems. The source of indoor aerosols can be natural or anthropogenic, leading to significant structural and compositional heterogeneity of inter-and intra-particles.…”
Section: Compositional Analysis Of Fine and Ultrafine Indoor Aerosol ...mentioning
confidence: 99%
“…Apart from the presence directly on environmental surfaces, the virus may survive for long periods in a variety of fluid suspensions 41 . Some have also suggested that in a highly endemic region for COVID‐19, widespread detection of virus may be possible for a large variety of public air and surfaces regardless of their constitution 35,42 . The latter study did not include an assessment for viable virus.…”
Section: Introductionmentioning
confidence: 99%
“… 41 Some have also suggested that in a highly endemic region for COVID‐19, widespread detection of virus may be possible for a large variety of public air and surfaces regardless of their constitution. 35 , 42 The latter study did not include an assessment for viable virus. Wastewater as a potential source or at least an indicator of disease prevalence is well studied.…”
Section: Introductionmentioning
confidence: 99%